2004
DOI: 10.1046/j.1600-0749.2003.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

During Human Melanoma Progression AP‐1 Binding Pairs are Altered with Loss of c‐Jun In Vitro

Abstract: We demonstrated previously that c‐Jun, JunB and c‐Fos RNA were dysregulated in metastatic melanoma cells compared with normal human melanocytes. The purpose of this study was to evaluate the distribution in composition of AP‐1 dimers in human melanoma pathogenesis. We investigated AP‐1 dimer pairing in radial growth phase‐like (RGP) (w3211) and vertical growth phase‐like (VGP) (w1205) human melanoma cells and metastatic cell lines (cloned from patients, c83‐2c, c81‐46A, A375, respectively) compared with melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Results from this current investigation, together with our previous observations that AP-1 composition has been altered during progression (Yamanishi et al, 1991;Yang et al, 2004), indicate that the abnormalities of AP-1 dimer composition in human melanoma cells may offer a unique preventive and therapeutic target for intervention of human melanoma.…”
Section: Ap-1 Composition Correlated With Melanoma Differentiation 307supporting
confidence: 68%
See 2 more Smart Citations
“…Results from this current investigation, together with our previous observations that AP-1 composition has been altered during progression (Yamanishi et al, 1991;Yang et al, 2004), indicate that the abnormalities of AP-1 dimer composition in human melanoma cells may offer a unique preventive and therapeutic target for intervention of human melanoma.…”
Section: Ap-1 Composition Correlated With Melanoma Differentiation 307supporting
confidence: 68%
“…To investigate whether elevated Fra-2 could interfere with MHC class I and Fas/CD95 expression, we also transiently overexpressed Fra-2 in human melanoma A375 cells, which only has JunD detectable in the AP-1 complex (Yang et al, 2004). The expression level of MHC class I and Fas/CD95 were detected by cytofluorometric analysis.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…The enrichment of DNA fragments displayed as peaks in the promoter/enhancer regions of specific target genes (ENCODE) were localized to the promoter/enhancer regions of FosB, NFATC2, WEE1, PVR, MAP1LC3B and LGALS3 [17][18][19][20][21][22] ( Fig. 2, Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…3A). Immunoblotting analysis showed that with nNOS depletion, the expression levels of JunD, MMP-1, APE/Ref-1, and Bcl-2 were significantly reduced, which are well-known genes that contribute to melanoma proliferation and invasion (58,59,61).…”
Section: Innovationmentioning
confidence: 99%